2019
DOI: 10.1007/s13361-018-02124-z
|View full text |Cite
|
Sign up to set email alerts
|

Electron Attachment and Electron Ionization of Formic Acid Clusters Embedded in Helium Nanodroplets

Abstract: We report the results of an experimental study of electron ionization of large helium nanodroplets doped with formic acid (FA). Several homologous series of cluster anions are observed, including [FA n -H] − , undissociated FA n − , and these ions complexed with one or more H 2 O. Some major features resemble those observed upon sputtering of frozen FA films but they differ significantly from results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 55 publications
(124 reference statements)
4
26
2
Order By: Relevance
“…Two recent studies by Mahmoodi-Darian et al investigated the interaction of HNDs doped with FA [389] as well as FA and C 60 with low-energy electrons (Fig. 2.25) [390].…”
Section: Complexes Of Formic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent studies by Mahmoodi-Darian et al investigated the interaction of HNDs doped with FA [389] as well as FA and C 60 with low-energy electrons (Fig. 2.25) [390].…”
Section: Complexes Of Formic Acidmentioning
confidence: 99%
“…The most abundant anion cluster series in the purely FA-doped droplet experiment was dehydrogenated [FA n -H] -, whereas for cations, protonated [FA n +H] + dominates the mass spectrum. Less abundant, but also observed are undissociated [FA n ] ± , deprotonated [FA n -H] + , and the more abundant ions complexed with one or more water molecules [389].…”
Section: Complexes Of Formic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that despite fragmentation of molecular dopants not being quenched by energy dissipation, fragmentation intermediates can be stabilized within the He matrix (Bartl et al, 2013). EI and PI were used in the past to analyze the behavior of a variety of atomic and molecular dopants such as Au (Martini et al, 2018), haloalkanes (Yang et al, 2006), rare gases (Kim et al, 2006), SF 6 (Peterka et al, 2006), H 2 O (Yang et al, 2007), acetic acid (da Silva, Jaksch, et al, 2009), CH 4 (Leidlmair, Bartl, et al, 2012), NaF (Weinberger et al, 2016), valine (Weinberger et al, 2016), C 60 (Goulart et al, 2017), or formic acid (Mahmoodi‐Darian et al, 2019). For a more comprehensive overview of the results of these investigations see ref.…”
Section: Ionization Of Doped Helium Dropletsmentioning
confidence: 99%
“…Since the ion source chamber pressure corresponds to that of single collision conditions, FAH + is formed by the break-up of an ionized formamide cluster, most probably from the ionized dimer. The observation of protonated parent (cluster) ions is characteristic for hydrogen-containing molecules and a highly abundant species upon electron ionization of clusters [37,[40][41][42][43][44][45]. The structures and energies of the neutral formamide dimer were the focus of few theoretical and experimental studies previously.…”
Section: Electron Ionization Of Bare Fa Clustersmentioning
confidence: 99%